FACTORS ASSOCIATED with EARLY SEX INTERCOURSE amoung YOUNG SCHOOLING CHILDREN in KICUKIRO DISTRICT- RWANDA. - ABELA, Anne M’lurhe; Francis, WABWIRE Paul (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Sex and sexuality among adolescents and young people have been reported to be on increase worldwide. The act is noted to take two directions as either by force (rape) or coation. As a result of this, significant number of adolescents (under age populations / < 20 years) is involved in sexual activities at an early age ( earlier than 20 years). Many young people are exposed to various risks such as unprotected sex, early pregnancy, STI/STDs, HIV/AIDS and early marriage that follows pregnancy. The aim of this study was to establish the degree of sexuality and identify the factors associated with early sexual action / practices among primary school children in Kicukiro District, Kigali City.